RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDE ABOUT BREAST CANCER WITH BREAST SELF-EXAMINATION (SADARI) IN ADOLESCENTS AT STATE SENIOR HIGH SCHOOL 1 DELI TUAA, DELI SERDANG DISTRICT YEAR 2024 - CHAIRANI, SHINTA ANDRIA; Sitepu, Marlen Sadrina (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2025)
Activity hormone especially estrogen hormone which is currently This Not yet stable cause teenager daughter potential experience abnormality Breasts . Teenagers menstruating daughter​ the first more fast own potential happen abnormality enough breasts​ big because of more beginning own the hormone estrogen and lasts longer his life . Techniques for recognize normal breast condition and knowing There is whether or not lumps that can trigger the occurrence of tumors or cancer breast in a way independent is understanding from Check Breast Alone (SADARI). For know Connection Knowledge and Attitude About Cancer Breast With Inspection Breast Self-Examination (SADARI) in Adolescents at SMA Negeri 1 Deli Tua, Deli Serdang Regency in 2024. Type of research used is cross sectional that is research that presses on time measurement or data analysis in one time. Respondent amount population will used as a sample , namely total sampling Where all over Teenagers in SMA Negeri 1 class X and XI Deli Tua, Deli Serdang Regency, as many as 30 respondents . The results of study This that is with knowledge p-value 0.003 which means There is connection between knowledge with inspection breast self-examination (SADARI) and attitude p-value 0.003 which means There is connection between knowledge with inspection breast yourself (SADARI). From the results study This expected inspection breast self (SADARI) is made as one of the effort detection early cancer breast .